Ascending Transtentorial Herniation: A Rare Complication of Posterior Cranial Fossa Tumors and Review of Literature - Velpula, Sreekanth; Goyal, Nishant (Asian Journal of Neurosurgery, 2025)
Cerebral herniation is the movement of brain tissue due to increased intracranial pressure. Ascending transtentorial herniation (ATH) is a rare consequence of lesions in the posterior cerebral fossa, often associated with obstructive hydrocephalus. Cerebrospinal fluid (CSF) diversion can alleviate symptoms but may also lead to ATH, particularly after ventriculoperitoneal (VP) shunt procedures. Despite its high mortality, early diagnosis and immediate intervention are crucial. This case report describes a child with a left cerebellar anaplastic ependymoma (CNS WHO grade 3) and obstructive hydrocephalus who developed ATH post-VP shunt and recovered after timely surgical decompression. A 3-year-old boy with a month-long history of headache without associated fever was diagnosed with a cystic lesion in the left cerebellar hemisphere, with obstructive hydrocephalus. Despite an initial plan to avoid CSF diversion, he experienced a hydrocephalic attack, leading to an emergency VP shunt procedure. Postsurgery, he showed signs of ATH and underwent immediate surgical decompression, resulting in a successful recovery and adequate brainstem decompression. In patients with posterior cranial fossa tumors with associated hydrocephalus, it is advisable to do upfront tumor excision and avoid a preoperative CSF diversion procedure. In the rare instance where a patient undergoes CSF diversion procedure before definitive surgery, early detection and immediate intervention are critical for reversing ATH and preserving brain function.
Keywords: ascending transtentorial herniation; hydrocephalus; posterior fossa tumor; ventriculoperitoneal shunt